2015
DOI: 10.1890/14-0581.1
|View full text |Cite
|
Sign up to set email alerts
|

Determining origin in a migratory marine vertebrate: a novel method to integrate stable isotopes and satellite tracking

Abstract: Stable isotope analysis is a useful tool to track animal movements in both terrestrial and marine environments. These intrinsic markers are assimilated through the diet and may exhibit spatial gradients as a result of biogeochemical processes at the base of the food web. In the marine environment, maps to predict the spatial distribution of stable isotopes are limited, and thus determining geographic origin has been reliant upon integrating satellite telemetry and stable isotope data. Migratory sea turtles reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
124
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(127 citation statements)
references
References 83 publications
1
124
2
Order By: Relevance
“…The isotopic data generated in this study adds to the growing body of work describing stable isotope baseline data for marine organisms in the eastern Pacific Ocean (Arthur et al, 2008;Olson et al, 2010;Ruiz-Cooley and Gerrodette, 2012;. A natural future direction would be to estimate marine isoscapes across taxa and trophic levels to provide a systematic framework for stable isotope ecological applications, as well as empirical studies of trophic dynamics (Somes et al, 2010;Ceriani et al, 2014;Vander Zanden et al, 2015;Magozzi et al, 2017;Kurle and McWhorter, 2017). A central repository of stable isotope data for sea turtles would support the advancement of this field and reduce duplication of efforts (Pauli, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…The isotopic data generated in this study adds to the growing body of work describing stable isotope baseline data for marine organisms in the eastern Pacific Ocean (Arthur et al, 2008;Olson et al, 2010;Ruiz-Cooley and Gerrodette, 2012;. A natural future direction would be to estimate marine isoscapes across taxa and trophic levels to provide a systematic framework for stable isotope ecological applications, as well as empirical studies of trophic dynamics (Somes et al, 2010;Ceriani et al, 2014;Vander Zanden et al, 2015;Magozzi et al, 2017;Kurle and McWhorter, 2017). A central repository of stable isotope data for sea turtles would support the advancement of this field and reduce duplication of efforts (Pauli, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…We broadly followed previously described methods (Ceriani et al 2012, Pajuelo et al 2012, Vander Zanden et al 2015) to predict foraging area using a discriminant function analysis (see Supplement 4), with a secondary classification method as per Zbinden et al (2011) to distinguish between 2 sites that were isotopically similar.…”
Section: Assigning Turtles To the Foraging Areasmentioning
confidence: 99%
“…With normal distributions found for the 3 isotopes, and the variance among foraging areas homo genous, we employed a linear discriminant function analysis. We used nonuniform priors using the number of turtles tracked to each site from the satellite telemetry (Royle & Rubenstein 2004, Vander Zanden et al 2015) and a posterior probability of assign ment set at 80%. The discriminant analysis was evaluated using the leave-one-out cross validation method with 95.7% of turtles from the training data correctly reclassified.…”
Section: Inferring Foraging Area Usementioning
confidence: 99%
See 1 more Smart Citation
“…C values in the 3 regions used by both species (northern, eastern and southern GoM) are not significantly different and therefore could not be differentiated (Vander Zanden et al 2015). (2) Vander Zanden et al (2015) also reported significant differences in δ 15 N between the northern GoM and the eastern and southern GoM.…”
mentioning
confidence: 98%